2017
DOI: 10.37358/rc.17.8.5765
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Oligoelements Content of Plant Material and Assessment of Bioactive Compounds from Calendula officinalis Lyophilized Extract

Abstract: The marigold extracts are used in traditional medicine for its anti-inflammatory, decongestive, antiseptic, antifungal, antimicrobial and immunostimulating properties. Existing studies have partially proved these properties, but are incomplete with regard to the possibility of standardizing the extract using the best working conditions so as it to be included in dietary supplements. The purpose of this study is to investigate the chemical composition of the marigold extracts, their contents in flavonoids and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…The ABTS value was obtained using the following equation based on the calibration curve: y = 1629 x + 98.94 (R 2 = 0.998), where x = absorbance and y= µmol Trolox equivalent [32,33]. Trolox was used as a standard solution, the calibration curve was made for concentrations between 0 and 300 µM, having a correlation coefficient R 2 = 0.9956 and the regression equation (y =0.0017x+0.0848), where x = absorbance registered at 595 nm and y = µmol Trolox equivalent [34][35][36].…”
Section: Abts Methodsmentioning
confidence: 99%
“…The ABTS value was obtained using the following equation based on the calibration curve: y = 1629 x + 98.94 (R 2 = 0.998), where x = absorbance and y= µmol Trolox equivalent [32,33]. Trolox was used as a standard solution, the calibration curve was made for concentrations between 0 and 300 µM, having a correlation coefficient R 2 = 0.9956 and the regression equation (y =0.0017x+0.0848), where x = absorbance registered at 595 nm and y = µmol Trolox equivalent [34][35][36].…”
Section: Abts Methodsmentioning
confidence: 99%
“…As standards were used metallogenic solutions of caffeic acid, having concentrations between 1 and 3 µg/mL), processed similarly to the samples. Absorbance was measured at 715 nm, read after 2 minutes of rest, in triplicate [19,[24][25][26][27][28][29]. The calibration curve ( fig.…”
Section: Snp Methods (Silver Nanoparticles)mentioning
confidence: 99%
“…After the addition of 100 µL of sample to 2900 µL ABTS + solution, the mixture was monitored spectrophotometrically at 734 nm. The calibration curve was made with the Trolox standard [15,16,26,[38][39][40].The calculation formula is the same as for the DPPH test.The reduction of The determination of total flavonoid contents The content of total flavonoids was determined by using a colorimetric method which has been described previously [25][26][27][28]. 1 mL of the sample (containing 0.1 mg / mL dry weight) is mixed with 4 mL water and placed in a 10 mL volumetric flask.…”
Section: Abts Methods (Determination Of Antioxidant Capacity Using Thementioning
confidence: 99%
“…Recent studies on antioxidants have demonstrated their important role in offset this imbalance [10,11]. Many antioxidant compounds possess antiinflammator y, antiatherosclerotic [12], antiproliferative, antitumor [13], antimutagenic, anticarcinogenic, antibacterial or antiviral activities [13][14][15][16][17][18]. An important group of antioxidants are phenolic compounds [10,12].…”
mentioning
confidence: 99%